Development of a framework for heritage conservation management of Arab District, Erbil, Iraq - Akram, Omar Khasro (2020)
Arab District has highly influenced Erbil city growth, contributing to its present shape and urban fabric form, though, historical urban areas and built cultural heritage are still treated as part of archaeological sites, where specific urban characteristics are not yet focused. Moreover, conservation, restoration and rehabilitation processes are also not clarified by the Law, leaving a gap between practical actions and official regulations. Confronting Arab District with the two active Laws for heritage management (National Policy of Iraq N.55 of 2002 and Local Policy of Kurdistan region N.08 of 2008), it is observed that unique values are put at risk, or even being lost, due to unclear directions and guidelines for conservation processes. Based on this problem, this research objectives are firstly to synthesise the best ICOMOS (International Council Of Monuments and Sites) charters that can be applied to conservation of heritage of Arab District, to analyse similar case references on conservation management to work as base for a framework design and, finally, to develop a framework for conservation management of heritage for Arab District, Erbil, Iraq, seeking to effectively control preservation projects. This research adopts literature review on tangible heritage, deeply identifying local and international regulations, analysing similar cases of conservation management on heritage and concepts of conservation management plans and frameworks to help on the design for Arab District. The adopted methodology lies on a case study, following a qualitative method that uses a Focused Group Discussion (F.G.D.), with a group of experts from different areas and fields, under heritage conservation, and online semi-structured questionnaires to a group of specialists, with many years of experience, to properly obtain results. This study contributes on proposing the concept of “conservation management plans, from case references in other Arab countries, where their similar problems have already been solved, could work as foundation for the development of a conservation management framework for tangible heritage in Arab District, Erbil, Iraq” and a conservation management framework with its evelopment recommendations. As key findings, the study identifies the Venice Charter, the Charter on Built Vernacular Heritage, the Washington Charter and the Burra Charter as some of the best ICOMOS charters belonging to conservation management for historic cities, including Arab District, providing reliable information for the framework development. The study of similar cases showed different approaches to answer the same type of problems and objectives, making it possible to isolate goals, strategy, actions, monitoring, level of responsibility and reference to policies as main framework components applied to specific themes of Arab District. This study helps not just specialists, such as decision-makers, stakeholders, planners, local government, archaeologists, and heritage professionals, but also, the society itself, including the general public, educators, and community group, having global impact towards humanity issues.